First principles study of structural equilibrium configuration of Ortho-, Meta-, and Para-chloroaniline molecules - Rai, Krishna Bahadur; Teemilsina, Nabin Kumar; Siwakoti, Bijay (Scientific World, 2024)
This work has studied the ground state energy, binding energy, equilibrium geometry, charge distribution, and dipole moment of ortho-, meta-, and para-chloroanilines using a wide range of advanced theoretical methods including first-principles Hartree-Fock (HF), Mϕller-Plesset (MP) perturbation theory, Configuration Interaction (CI) and Density Functional Theory [DFT (B3LYP)] with basis sets 3-21G, 4-31G, 6-31G, 6-31G*, 6-31G**, 6-311G, 6-311G*, and 6-311G**. The trend in ground state energy is obtained in EDFT < EHF+MP3 < EHF+MP2 < ECISD < EHF. The calculated binding energies for these molecules in DFT calculations using the 6-311G** basis set are determined to be 7590.61 KJ/mol, 7589.14 KJ/mol, and 7586.73 KJ/mol respectively. The positive binding energy values occur in all these molecules indicate the stability of the molecule. The bond length between carbon (C) and chlorine (Cl) in ortho, meta and para chloroaniline is determined to be 1.769 Å, 1.765 Å, and 1.765 Å respectively. In calculation at the HF+MP2 level, the C-Cl bond length for ortho, meta, and para chloroaniline molecules are determined to be 1.742 Å, 1.741 Å, and 1.740 Å respectively. There is a reduction in the C-Cl bond length when the chlorine atom's position in chloroaniline changes from ortho to meta and then to para positions. The values of bond angle and dihedral angle for these molecules at the HF, HF+MP2, and DFT (B3LYP) levels of calculation are nearly equal. The distribution of charges in each molecule results in a net sum of Mulliken charges equal to zero. The calculated dipole moments for ortho, meta, and para chloroaniline molecules are 2.1194 Debye, 3.5398 Debye, and 4.1385 Debye, respectively.